If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -11 = 1 + -1x Reorder the terms: -11 + 3x = 1 + -1x Solving -11 + 3x = 1 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -11 + 3x + x = 1 + -1x + x Combine like terms: 3x + x = 4x -11 + 4x = 1 + -1x + x Combine like terms: -1x + x = 0 -11 + 4x = 1 + 0 -11 + 4x = 1 Add '11' to each side of the equation. -11 + 11 + 4x = 1 + 11 Combine like terms: -11 + 11 = 0 0 + 4x = 1 + 11 4x = 1 + 11 Combine like terms: 1 + 11 = 12 4x = 12 Divide each side by '4'. x = 3 Simplifying x = 3
| 5(y-2)-y=42 | | 1.3(x)=5 | | 8m-27=28 | | a-4/3=2a+2/3 | | 7x-8+1=8-9+7x | | 3x+1=30 | | 4x-8=6x-16 | | 5x+6z=4+8y | | 40=x-23 | | 5.99x+2.05=8.45 | | 1.62+7n=4n+2.7n | | 13x+18=70 | | 3(u+9)=8u-8 | | x^2-1=2x+4 | | 2(y+5)=18 | | 50(p+20)=20(p+10) | | 10w=4000 | | -7x-3x+2=-8+8 | | x+5sqrt(x)-14=0 | | 2(3y+1)=14+3y | | (4a^2+9b^5)-(-2a^2-6b^5)= | | 18-6k=-7(2+2k) | | 3sinx+4cosx=1 | | 666+x=1 | | 3x+y=252.19 | | 9x^2+7=385 | | .75(3x-16)+.75x=5.33333333333 | | -17-5n=6(2+5n)+6 | | 8x^2=4x-1 | | 4x+4-x-1=1 | | Ln(7x-1)=3 | | 5x^2-9=11 |